Finansowanie placówek medycznych ze środków unijnych w okresie programowania 2007-2013 - Baran, Wioletta; Dernoga, Agnieszka; Jarco, Wioletta (Financing Medical Institutions From the Eu Funds in the Programming Period 2007-2013, 2008)
Poland's membership in the European Union provides an opportunity for using additional financial resources. The article aims to show operational programmes which could be used for financing medical institutions in different areas of their activities. The analysis of programmes documents indicates that medical institutions can apply for financial support in the area of infrastructure development. At the same time, they can apply for financial support for increasing the availability of medical information as well as for training of medical and management staff.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 195-205